To: Teacher2Teacher Public Discussion
Subject: Re: Re: Re: HELP;removing common factor!
Sarah, that is a nice proof. At first I was confused but finally saw the light. On your third step you factored out the common factor. On my proof, I noticed that a!/(a-1!) = a. That may not be obvious to some, but here is an example. Let a=7, then a!=1x2x3x4x5x6x7 Then (a-1)!= 1x2x3x4x5x6 So that 1x2x3x4x5x6x7 -------------- = 7 1x2x3x4x5x6
Math Forum Home || The Math Library || Quick Reference || Math Forum Search